Impact of Plea-Bargaining on the Criminal Justice System in Takum Metropolis - Stephen, Charity; Fadahunsi, John A. (Darul Yasin Al Sys, 2025)
The study examines impact of plea bargaining on the criminal justice system in Takum Metropolis. The objectives of the study were to assess the impact of plea bargaining on the efficiency of the criminal justice system in Takum Metropolis, Taraba State and identify the challenges and barriers to effective implementation of plea bargaining in Takum Metropolis, Taraba State. The study adopted the use of descriptive survey research design. The sample size for the study was 46 respondents which was the total number of staff working in Nigeria Correctional Service Medium Security Custodial Center Takum (NCSMSCCT) and the Magistrate Court Takum (MCT). The sampling technique adopted for the study was total census sampling technique. Data for the study from the study was collected through the use of structured questionnaires and oral interview. Findings from the study revealed that plea bargain has an overwhelming impact on the administration of criminal justice system in Takum Local Government Area. is a veritable catalyst for speedy trial. Further findings from the study also revealed that there are challenges and barriers to effective implementation of plea bargaining in Takum L.G.A plea bargaining in Takum Local Government. Notable among these challenges is the issue of lack of understanding of plea bargaining among stakeholders in Takum Metropolis. It was recommended that Takum Judicial System should establish a robust oversight mechanism to monitor plea bargaining agreements, ensuring they are not used to protect corrupt public officials and also launch public awareness campaigns to educate citizens about the plea-bargaining process, its benefits, and its limitations.